Between Western Philosophy and Islamic Philosophy : An Effort to Examine The Common Point and The Point of Difference - Amril amril; Fuad Mahbub Siraj; Endrika Widdia Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
This study wants to analyze the common points and the points of difference between Western and Islamic philosophy. This is qualitative research using the exploratory-analytical method. This study finds that Western and Islamic philosophy has contributed to each other. The common point between Western and Islamic Philosophy lies in transmitting the truth. Meanwhile, we can see the point of difference in three aspects. First is the source of knowledge. Western philosophy comes from reason and the five senses, while Islamic philosophy is not only that but also from authority (al-Quran and al-Sunnah). Second, the characteristics of knowledge. Characteristics of knowledge in Western philosophy, namely, skeptical, rational-empirical, dichotomous, and positivistic-objective; while in Islamic Philosophy, namely, Qur'anic, harmonization of reason and revelation, theocentric, and value point of view. The third is the truth value of knowledge. The truth value of knowledge in Western philosophy is relative, while Islamic philosophies are absolute and some are relative.